POLA PERSARANGAN CURIK BALI (Leucopsar rothscliildiStresemann, 1912) DAN KERAB ATNYA DI TAMAN NASIONAL BALI BARAT - Noerdjito, Mas (Research Center for Biology-Indonesian Institute of Sciences, 2005)
Bali myna (Leucopsar rothschildi Stresemann, 1912) was reported as an endemic bird from western part of Bali Island, and also as endangered species.The species lived in the lowland forest and used tree holes made by other animals as their nests.Besides L.rothschildi, there were two other species of birds found using the holes as their nest in the study site, namely Black-winged starling(Sturnus melanopterus (Daudin, 1800)) and Javan myna (Acridotheres fitscus (Wagler, 1827)).This paper deals with result of research on the competition of those three species of birds in obtaining tree hole for nesting, was carried out in West Bali National Park, Bali. Data demonstrated that there were no differences in the size of nest for the three species of birds, Javan myna lived in the habitat of coconut garden where Bali myna did not occupy it, and the habitat of Black-winged starling was overlapped with Bali myna, but Bali myna preferred living in denser vegetation. The reproduction of the three species of birds were dependent on the occurrence of other birds species belonging to Picidae and Capitonidae who were able to make holes on trees.